Corrective Intra-articular Osteotomies for Tibial Plateau Malunion - Kfuri, Mauricio; Schatzker, Joseph (The Journal of Knee Surgery, 2017)
Anatomical reduction of the articular surface, restoration of mechanical axis, and containment of articular rim are the goals of the treatment of tibial plateau fractures, with an ultimate aim to restore joint congruity and stability. Tibial plateau malunions or nonunions are a result of a failed treatment. This article aims to review the most typical failure models and some strategies to overcome them by using joint preservation surgical techniques.
Keywords: tibial plateau; malunion; nonunion; failure; osteotomy